Penggunaan Model Pembelajaran Problem Based Learning (PBL) Untuk Meningkatkan Hasil Belajar IPAS Peserta Didik Kelas III SDN 01 Muara Panas Kabupaten Solok - Zulkim, Syahira Nabila; Sartono, Sartono; Arwin, Arwin; Zahara, Leni (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to describe how the use of the Problem Based Learning (PBL) model in science learning to improve the learning outcomes of class III students of SDN 01 Muara Panas, Solok Regency. This research is a Classroom Action Research (CAR) using a qualitative approach, which is carried out in two cycles, namely cycle I (two meetings) and cycle II (one meeting) carried out in four stages, planning, implementation, observation and reflection. The subjects of this study were teachers and class III students of SDN 01 Muara Panas, Solok Regency with a total of 12 students, 6 boys and 6 girls. The results of this study showed an increase in the teaching module in cycle I with a percentage of 87.49% (A) and cycle II 95.83% (A). Assessment of teacher activity in cycle I with a percentage of 78.56% (B) and cycle II 96.42% (A). Assessment of student activity in cycle I with a percentage of 78.56% (B) and cycle II 96.42% (A). Assessment of students in improving learning outcomes in cycle I obtained an average of 72.49 (C) and cycle II with an average of 85,07 (B). Based on these results, it can be concluded that the Problem Based Learning (PBL) model can improve science learning outcomes in class III.